The Design, Implementation, and Audit of Occupational Health and Safety Management Systems - McKinnon, Ron C. (Milton : CRC Press LLC, 2019)
This book covers the design, implementation, and auditing of structured occupational health and safety management systems (SMS), sometimes referred to as safety programs. Every workplace has a form of SMS in place as required by safety regulations and laws. The Design, Implementation, and Audit of Occupational Health and Safety Management Systems describes some of the elements that constitute an SMS, the implementation process, and the auditing of the conformance to standards. It covers more than 60 processes, programs, or standards of a system, and gives important background information on each element. Guidelines and examples show how to design and implement the risk-based processes, programs and standards, and how to audit them against standards. The text is based on actual SMS implementation experiences across a wide range of industries. It offers a roadmap to any organization which has no structured SMS. It will guide them through the process of upgrading their health and safety processes to conform to local and international standards. It will lead them away from relying on reactive safety measures such as injury rates, to proactive actions which are measured by the audit of the system. Features Covers more than 60 elements of a safety management system (SMS) Provides practical examples of how to design, implement, and audit a structured SMS Based on actual SMS implementation experience across a wide range of industries Presents the integration of an SMS into the day-to-day functions of the organization
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Environmental Engineering & Technology; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; Industrial safety -- Management; Industrial safety -- Auditing; Industrial safety -- Standards; Industrial hygiene -- Management; Industrial hygiene -- Auditing; Industrial hygiene -- Standards